Hematological Characteristics of Ducks (Cairina moschata) of Southeastern Nigeria - Igwe, GOI.; Okoli, IC.; Okeudo, NJ. (Tropicultura, 2003)
Morning (9-10 am) blood samples collected through the wing veins of six males and six females clinically healthy adult ducks (Cairina moschata) were used to study the hematological profile and serum chemistry of southeastern Nigerian ducks. Packed cell volume (PCV) and hemoglobin concentration (HBC) means were 46.00 ± 1.73%, 41.17 ± 3.13% and 15.67 ± 0.29 g%, 14.17 ± 1.13 g% for drakes and ducks respectively indicating significant differences (P< 0.01) between male and female values. Mean erythrocytes sedimentation rate (ESR) of the drakes (1.63 ± 0.35 mm/hr.) was significantly different (P< 0.05) from the 1.95 ± 0.30 mm/hr observed in the ducks. Male and female blood coagulation time (BCT) and mean corpuscular hemoglobin concentration (MCHC) values were 1.55 ± 1.00 and 1.85 ± 11.05 seconds and 34.07 ± 1.01%, 34.42 ± 2.13% respectively. Leukocyte count indicated no significant difference (P> 0.05) between the males and females. Again, hetrophils and lymphocytes counts did not reveal significant differences (P> 0.05) between the male and female birds. The mean serum protein value of the females (12.07 ± 1.59/100 ml) was significantly higher (P< 0.01) than the 6.87 ± 0.42 g/100 ml recorded in males. Mean serum calcium and phosphorous levels were also significantly different (P< 0.01) at 7.43 ± 0.75 mg/dl, 8.52 ± 0.58 mg/dl and 3.20 ± 1.51 mg/dl, 7.98 ± 1.39 mg/dl in the males and females respectively.